Community College Pathways for Disadvantaged Students - Harry J. Holzer; Zeyu Xu (Institute of Labor Economics (IZA), 2019)
In this paper we estimate the impacts of the "pathways" chosen by community college students - in terms of desired credentials and fields of study, as well as other choices and outcomes along the paths - on the attainment of credentials with labor market value. We focus on the extent to which students change their choices over time, whether students make well-informed choices, and the impacts of choices on outcomes. We find that several characteristics of chosen pathways, such as field of study and desired credential as well as early "momentum," affect outcomes. Student choices of pathways are not always driven by information about later chances of success, in terms of probabilities of completing programs and attaining strong earnings. Students also change pathways quite frequently, making it harder to accumulate needed credits in their fields. Attainment of credentials with greater market value could thus likely be improved by appropriate guidance and supports for students along the way, and perhaps by broader institutional changes as well.
Keywords: I2; 330; community college; pathways; labor market; earnings